Determination of the internal quantum efficiency for photoelectrochemical reaction in a semiconductor photoelectrode by photoacoustic detection - Murakami, Naoya; Okuzono, Keita (Chemical communications (Cambridge, England), 2020)
We showed for the first time the validity of photothermal measurement for determination of internal quantum efficiency, which is one of the most fundamental parameters for energy conversion systems. The measurement method using photoacoustic detection in the present study can be applied to a wide variety of samples and measurement conditions. We report a method for the determination of internal quantum efficiency for photoelectrochemical reaction in a semiconductor photoelectrode by photoacoustic detection.